2011
DOI: 10.4314/mejs.v3i2.67711
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Groundwater Quality for Irrigation with Reference to Hand Dug Wells, Hantebet Catchment, Tigray, Northern Ethiopia

Abstract: The purpose of the project has been to assess the suitability of groundwater quality for irrigation purpose in the Hantebet catchment (24.4 km 2), Tigray region, northern Ethiopia. The total numbers of hand dug wells in the area are 154. Out of these, 110 are functional and the remaining dried out. Stratified and random sampling techniques were utilized to select representative samples of groundwater. Accordingly, twenty groundwater samples were collected from twenty hand dug wells for chemical analysis. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The emphasis is especially focused on regional and local studies on groundwater suitability for irrigation purposes, resulting in numerous investigations based on different hydrogeochemical tools and indices (e.g. Watanabe et al, 2008;Tadesse et al, 2010;Ravikumar et al, 2011;Romanelli et al, 2012). Nonetheless, studies on the impact of irrigation on groundwater quality are mainly related to the assessment of diffuse pollution impact on groundwater quality, especially associated with fertilizers use and farming activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis is especially focused on regional and local studies on groundwater suitability for irrigation purposes, resulting in numerous investigations based on different hydrogeochemical tools and indices (e.g. Watanabe et al, 2008;Tadesse et al, 2010;Ravikumar et al, 2011;Romanelli et al, 2012). Nonetheless, studies on the impact of irrigation on groundwater quality are mainly related to the assessment of diffuse pollution impact on groundwater quality, especially associated with fertilizers use and farming activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…ese slight variations in the concentrations might be due to different levels of chloride salts in the soil and sediments or a result of differences in degree of wastes entering into the hand-dug wells [32]. e findings of this study are similar to hand-dug wells in Hantebet Catchment, Tigray, and Northern Ethiopia, varying from 15.45 to 49.44 mg/L [33]. Chloride value has a positive strong correlation with sulfate ion (r � 0.997) and nitrate ion (r � 0.982).…”
Section: Chloride Ionmentioning
confidence: 58%
“…The result showed that the study area was found at lower elevation than Tita Meteorological Station. So, the temperature data from Tita Meteorological Station was extrapolated to the study area by allowing an increment of 0.6 ºC for 100 m (Nata, 2006). The mean minimum (min) monthly, the mean maximum (max) monthly, and the mean annual temperature was presented below in table 6.…”
Section: Thiessen Polygon Interpolationmentioning
confidence: 99%